SISTEM INFORMASI MONITORING REALISASI ANGGARAN BELANJA UNTUK PERCEPATAN PENYERAPAN APBD DI KECAMATAN KRANGGAN - Litafira Syahadiyanti; Aulia Aissudibyo; Slamet Kacung; Pamudi (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2025)
The Budget Realization Monitoring Information System for Accelerating APBD Absorption in Kranggan Sub-district is developed to oversee budget activities by considering the realization achievements and absorption issues encountered during implementation. With this system, the sub-district head, as the policymaker, will be able to obtain detailed information on budget absorption at the village level for each sub-activity and will also be able to present the obstacles that hinder the implementation of activities based on data input from the villages. With the data provided by this information system, the sub-district administration will be able to plan further actions to address the issues and accelerate budget absorption efficiently. The methodology used in this research is Extreme Programming (XP), with the System Usability Scale (SUS) evaluation model and Blackbox testing for system testing. The results of this study show that the system successfully displays real-time budget realization data every month in the form of financial reports, provides data required for the evaluation of budget absorption acceleration, and presents reports on the obstacles experienced by villages in budget absorption. The outcome not only improves transparency and accountability in budget management but also provides an effective tool for evaluating and improving the budget absorption process at the village level.